A systematic review on treatment‐related mucocutaneous reactions in COVID‐19 patients - Najar Nobari, Niloufar (Dermatol Ther, 2020)
Most of drugs could have certain mucocutaneous reactions and COVID‐19 drugs are not an exception that we focused. We systematically reviewed databases until August 15, 2020 and among initial 851 articles, 30 articles entered this study (20 case reports, 4 cohorts, and 6 controlled clinical trials). The types of reactions included AGEP, morbiliform drug eruptions, vasculitis, DRESS syndrome, urticarial vasculitis, and so on. The treatments have been used before side effects occur, included: antimalarial, anti‐viral, antibiotics, tocilizumab, enoxaparin and and so on. In pandemic, we found 0.004% to 4.15% of definite drug‐induced mucocutaneous reactions. The interval between drug usage and the eruption varied about few hours to 1 month; tightly dependent to the type of drug and hydroxychloroqine seems to be the drug with highest mean interval. Antivirals, antimalarials, azithromycin, and tocilizumab are most responsive drugs for adverse drug reactions, but antivirals especially in combination with antimalarial drugs are in the first step. Types of skin reactions are usually morbilliform/exanthematous maculopapular rashes or urticarial eruptions, which mostly may manage by steroids during few days. In the setting of HCQ, specific reactions like AGEP should be considered. Lopinavir/ritonavir is the most prevalent used drug among antivirals with the highest skin adverse reaction; ribarivin and remdisivir also could induce cutaneous drug reactions but favipiravir has no or less adverse effects. Logically the rate of dermatologic adverse effects among anivirals may relate to their frequency of usage. Rarely, potentially life‐threatening reactions may occur. Better management strategies could achieve by knowing more about drug‐induced mucocutaneous presentations of COVID‐19.